2018
DOI: 10.4236/tel.2018.83019
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Relationship between Floods and Poverty: The Case of Region of Dakar

Abstract: Since 2005 in Senegal, progress in reducing poverty has stagnated. Successive exogenous shocks and a slowdown in reforms have, in part, reduced average growth to 3.3%, a rate barely above that of population growth (2.5%). Exogenous shocks include floods, which have become recurrent in the country's major cities, but especially in the capital Dakar, where they remain an omnipresent reality. These floods, with heavy consequences sometimes even disastrous (damage and loss of human life), are one of the main reaso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 10 publications
1
6
0
1
Order By: Relevance
“…Land tenure ensures household security and survival, both now and for future generations. Furthermore, land tenure rights across the Dakar metropolitan region are expensive, and residents reported that land prices in Djida Thiaroye Kao were out of reach for most, despite often being classified as an undesirable place to live [32]. This finding suggests that tenure rights are considered essential to many residents, and that moving without guarantee of tenure is undesirable.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Land tenure ensures household security and survival, both now and for future generations. Furthermore, land tenure rights across the Dakar metropolitan region are expensive, and residents reported that land prices in Djida Thiaroye Kao were out of reach for most, despite often being classified as an undesirable place to live [32]. This finding suggests that tenure rights are considered essential to many residents, and that moving without guarantee of tenure is undesirable.…”
Section: Discussionmentioning
confidence: 99%
“…Not only does Pikine suffer from development and environmental problems that contribute to flooding, it also faces economic and social challenges. In 2005, just as increased rainfalls were causing regular flooding, Senegal's poverty reduction efforts stalled [32]. The floods themselves are one explanation for this decline in economic growth.…”
Section: Urban and Economic Development Of Pikinementioning
confidence: 99%
See 1 more Smart Citation
“…Poor drainage in urban informal settlements also results in higher susceptibility to flooding, which is associated with more acute human exposure risks 63 . These settlements are more likely to be located in low-lying, flood-prone areas than higher income neighborhoods of the same cities [64][65][66] . A recent mapping-based study in Ho Chi Minh City, Vietnam, estimated that 83% of urban informal settlement areas were exposed to floods (for a 1000-year return period) compared to 68% of the city as a whole 65 , not considering the impacts of flood protections such as drainage systems that are unlikely to be equitably distributed between urban informal settlements and wealthier neighborhoods 63 .…”
Section: Insufficient Drinking Water Drainage and Sanitation Infrastmentioning
confidence: 99%
“…The more representative ones are the big propulsion theory, the low level equilibrium trap theory, the poverty vicious circle theory, the minimum effort proposition theory, etc. [1,2] . Because the theory assumes that the conditions are very demanding, the theoretical model is too idealistic and far from the actual situation.…”
Section: Introductionmentioning
confidence: 99%